‘Get in touch with yourself’: The Structure of Relationship Advice in Women’s Magazines - Reem Adib Lulu; Sohayle M. Hadji Abdul Racman (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2021)
This study investigates the way sex and relationship advice articles are structured in four English language women’s magazines. Cosmopolitan and Marie Claire were selected from the US, and Female and Her World from Malaysia. Forty articles were selected for the analysis. The study adopts Machin and Van Leeuwen’s (2003) problem-solution structure, besides using discourse pragmatic analysis. By studying this genre in the two different contexts, one of the main things that emerged is that this particular genre is more complex and diverse than what other researchers have found. The writers of the advice resort to various strategies and techniques to attract women to read these articles. They also have to balance social and cultural sensitivities with their message of freedom and liberation for women as appeared in the Malaysian data. Thus, studying this genre gives useful insights on how culture affects the texts and vice-versa.